Correlation between Seebeck coefficients and electronic structures of nitrogen- or boron-doped reduced graphene oxide via thermally activated carrier transport. Issue 32 (27th June 2018) - Bark, Hyunwoo; Lee, Wonmok; Lee, Hyunjung
Abstract : In this study, we report the relative electronic structure of thermally reduced graphene oxide (TrGO) using energy-dependent Seebeck coefficient. Abstract : In this study, we report the energy-level-dependent Seebeck coefficients of thermally reduced graphene oxide (TrGO) measured using a field-effect transistor with a microheater. B- or N-doped TrGO samples were prepared using graphene oxide (GO) solutions containing 10 or 50 mM boric acid or urea. In addition, heavily N-doped TrGO was prepared by annealing GO under an Ar/NH3 atmosphere. During thermal annealing, boric acid and urea decomposed and B and N atoms were doped onto TrGO. The gate-dependent conductance of the samples was measured first. In general, all the samples exhibited ambipolar behavior. However, as a function of doping state, the gate-dependent conductance differed slightly in comparison with that of TrGO. B-TrGO exhibited more intensive hole transport, whereas N-TrGO exhibited more intensive electron transport. In addition, the conductance was investigated as a function of ambient temperature for evaluating bandgap opening by the doping effect. When the gate bias was changed from −80 to 80 V, the Seebeck coefficient of TrGO changed from 4 to −2 μV K −1, which indicates that the carrier transport was changed from hole to electron transport depending on the energy state. However, impurity-doped TrGO (B- or N-TrGO) exhibited different behaviors. The Seebeck coefficient of B-TrGO changed from 20 to −4 μV K −1, whereas that of N-TrGO changed from 4 to −10 μV K −1 in a similar range of gate bias. Notably, the Seebeck coefficient of heavily N-doped TrGO changed from −8 to −18 μV K −1 in a similar range of gate bias. On the basis of the Seebeck coefficients and relative bandgaps of TrGO, B-doped TrGO, and N-doped TrGO, the approximate relative electronic structure of TrGO was deduced.